Circulating MicroRNAs and Long Non-coding RNAs as Potential Diagnostic Biomarkers for Parkinson’s Disease - Yang, Yimin (Front Mol Neurosci, 2021)
Parkinson’s disease (PD) is the world’s second most common neurodegenerative disease that is associated with age. With the aging of the population, patients with PD are increasing in number year by year. Most such patients lose their ability to self-care with disease progression, which brings an incalculable burden to individual families and society. The pathogenesis of PD is complex, and its clinical manifestations are diverse. Therefore, it is of great significance to screen for circulating biomarkers associated with PD to reveal its pathogenesis and develop objective diagnostic methods so as to prevent, control, and treat the disease. In recent years, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are considered to be effective biomarkers for various diseases due to their stability, and resistance to RNAase digestion and extreme conditions in circulating fluids. Here, we review recent advances in the detection of abnormally expressed miRNAs and lncRNAs in PD circulating fluids, and discuss the function and molecular mechanisms of plasma or serum miR-124, miR-132, miR-29, miR-221, miR-7, miR-433, and miR-153 in the regulation and progression of PD. Additionally, application of the differential expression of lncRNAs in circulating fluid in the pathological progression and diagnosis of PD is also reviewed. In short, the determination of abnormally expressed circulating miRNAs and lncRNAs will be valuable for the future diagnosis and treatment of PD.